- #1

- 208

- 0

I have been trying to derive

I set up a collision between 2 same balls (##m_1 = m_2 = m##). Before the collision these two balls travel one towards another in ##x## direction with velocities ##{v_1}_x = (-{v_2}_x) = v##. After the collision these two balls travel away from each other with velocity ##{v_1}_y = (-{v_2}_y) = v##. Coordinate system travells from left to right with velocity ##u=v##

Please see the pictures below where picture (a) shows situation before collision and picture (b) after collision.

http://shrani.si/f/2A/m3/4kDXDQo1/momentum.png [Broken]

Below is a proof that Newtonian momentum ##mv## is not preserved in coordinate system ##x'y'##. I used ##[\, | \,]## to split ##x## and ##y## components. ##p_z'## is momentum before collision where ##p_k'## is momentum after collision.

[itex]

\scriptsize

\begin{split}

p_z' &= \left[ m_1 {v_1}_x' + m_2 {v_2}_x'\, \biggl| \, 0 \right] = \left[ m_1 0 + m_2 \left( \frac{{v_2}_x - u}{1-{v_2}_x\frac{u}{c^2}} \right)\, \biggl| \, 0 \right]= \left[ m \left( \frac{-v - v}{1+ v \frac{v}{c^2}} \right) \, \biggl| \, 0 \right] \\

p_z' &= \left[ - 2mv \left( \frac{1}{1+ \frac{v^2}{c^2}}\right) \, \biggl| \, 0 \right]

\end{split}

[/itex]

[itex]

\scriptsize

\begin{split}

p_k' &= \left[-2mv \, \biggl| \,m_1 {v_1}_y' + m_2 {v_2}_y'\right]=\left[ -2mv \, \biggl| \, m_1 \left( \frac{{v_1}_y}{\gamma \left(1 - {v_1}_y \frac{u}{c^2}\right)} \right) + m_2 \left( \frac{{v_2}_y}{\gamma \left(1 - {v_2}_y \frac{u}{c^2}\right)} \right) \right]\\

p_k' &= \left[ -2mv \, \biggl| \, m \left( \frac{v}{\gamma \left(1 - v \frac{v}{c^2}\right)} \right) - m \left( \frac{v}{\gamma \left(1 - v \frac{v}{c^2}\right)} \right)\right]\\

p_k' &= \left[ -2mv \, \biggl| \, 0 \right]

\end{split}

[/itex]

It is clear that ##x## components differ by factor ##1/\left(1+\frac{v^2}{c^2}\right)##.

In the proof above I used velocity transformations derived below (derivation is taken from here):

[itex]

v_x' = \frac{dx'}{dt'}=\frac{\gamma (d x - u d t)}{\gamma \left(d t - d x \frac{u}{c^2} \right)} = \frac{d x - u d t}{d t - d x \frac{u}{c^2}} = \frac{\frac{d x}{d t} - u \frac{d t}{d t}}{\frac{d t}{d t} - \frac{d x}{d t} \frac{u}{c^2}} \Longrightarrow \boxed{v_x' = \frac{v_x - u}{1- v_x \frac{u}{c^2}}}

[/itex]

[itex]

v_y' = \frac{dy'}{dt'}=\frac{d y}{\gamma \left(d t - d x \frac{u}{c^2} \right)} = \frac{\frac{dy}{dt}}{\gamma \left(\frac{dt}{dt} - \frac{dx}{dt} \frac{u}{c^2} \right)} \Longrightarrow \boxed{v_y' = \frac{v_y}{\gamma \left(1 - v_x \frac{u}{c^2} \right)}}

[/itex]

**why**relativistic momentum is defined as ##p=\gamma mv##.I set up a collision between 2 same balls (##m_1 = m_2 = m##). Before the collision these two balls travel one towards another in ##x## direction with velocities ##{v_1}_x = (-{v_2}_x) = v##. After the collision these two balls travel away from each other with velocity ##{v_1}_y = (-{v_2}_y) = v##. Coordinate system travells from left to right with velocity ##u=v##

**at all times**(after and before collision).Please see the pictures below where picture (a) shows situation before collision and picture (b) after collision.

http://shrani.si/f/2A/m3/4kDXDQo1/momentum.png [Broken]

Below is a proof that Newtonian momentum ##mv## is not preserved in coordinate system ##x'y'##. I used ##[\, | \,]## to split ##x## and ##y## components. ##p_z'## is momentum before collision where ##p_k'## is momentum after collision.

[itex]

\scriptsize

\begin{split}

p_z' &= \left[ m_1 {v_1}_x' + m_2 {v_2}_x'\, \biggl| \, 0 \right] = \left[ m_1 0 + m_2 \left( \frac{{v_2}_x - u}{1-{v_2}_x\frac{u}{c^2}} \right)\, \biggl| \, 0 \right]= \left[ m \left( \frac{-v - v}{1+ v \frac{v}{c^2}} \right) \, \biggl| \, 0 \right] \\

p_z' &= \left[ - 2mv \left( \frac{1}{1+ \frac{v^2}{c^2}}\right) \, \biggl| \, 0 \right]

\end{split}

[/itex]

[itex]

\scriptsize

\begin{split}

p_k' &= \left[-2mv \, \biggl| \,m_1 {v_1}_y' + m_2 {v_2}_y'\right]=\left[ -2mv \, \biggl| \, m_1 \left( \frac{{v_1}_y}{\gamma \left(1 - {v_1}_y \frac{u}{c^2}\right)} \right) + m_2 \left( \frac{{v_2}_y}{\gamma \left(1 - {v_2}_y \frac{u}{c^2}\right)} \right) \right]\\

p_k' &= \left[ -2mv \, \biggl| \, m \left( \frac{v}{\gamma \left(1 - v \frac{v}{c^2}\right)} \right) - m \left( \frac{v}{\gamma \left(1 - v \frac{v}{c^2}\right)} \right)\right]\\

p_k' &= \left[ -2mv \, \biggl| \, 0 \right]

\end{split}

[/itex]

It is clear that ##x## components differ by factor ##1/\left(1+\frac{v^2}{c^2}\right)##.

**QUESTION:**I want to know why do we multiply Newtonian momentum ##p=mv## by factor ##\gamma = 1/ \sqrt{1 - \frac{v^2}{c^2}}## and where is the connection between ##\gamma## and factor ##1/\left(1+\frac{v^2}{c^2}\right)## which i got?**FURTHER EXPLAINATION:**In the proof above I used velocity transformations derived below (derivation is taken from here):

[itex]

v_x' = \frac{dx'}{dt'}=\frac{\gamma (d x - u d t)}{\gamma \left(d t - d x \frac{u}{c^2} \right)} = \frac{d x - u d t}{d t - d x \frac{u}{c^2}} = \frac{\frac{d x}{d t} - u \frac{d t}{d t}}{\frac{d t}{d t} - \frac{d x}{d t} \frac{u}{c^2}} \Longrightarrow \boxed{v_x' = \frac{v_x - u}{1- v_x \frac{u}{c^2}}}

[/itex]

[itex]

v_y' = \frac{dy'}{dt'}=\frac{d y}{\gamma \left(d t - d x \frac{u}{c^2} \right)} = \frac{\frac{dy}{dt}}{\gamma \left(\frac{dt}{dt} - \frac{dx}{dt} \frac{u}{c^2} \right)} \Longrightarrow \boxed{v_y' = \frac{v_y}{\gamma \left(1 - v_x \frac{u}{c^2} \right)}}

[/itex]

Last edited by a moderator: